Effects of biphasic, basal-bolus or basal insulin analogue treatments on carotid intima-media thickness in patients with type 2 diabetes mellitus: the randomised Copenhagen Insulin and Metformin Therapy (CIMT) trial. Issue 2 (25th February 2016) - Lundby-Christensen, Louise; Vaag, Allan; Tarnow, Lise; Almdal, Thomas P; Lund, Søren S; Wetterslev, Jørn; Gluud, Christian; Boesgaard, Trine W; Wiinberg, Niels; Perrild, Hans; Krarup, Thure; Snorgaard, Ole; et al.
Abstract : Objective: To assess the effect of 3 insulin analogue regimens on change in carotid intima-media thickness (IMT) in patients with type 2 diabetes. Design and setting: Investigator-initiated, randomised, placebo-controlled trial with a 2×3 factorial design, conducted at 8 hospitals in Denmark. Participants and interventions: Participants with type 2 diabetes (glycated haemoglobin (HbA1c )≥7.5% (≥58 mmol/mol), body mass index >25 kg/m 2 ) were, in addition to metformin versus placebo, randomised to 18 months open-label biphasic insulin aspart 1–3 times daily (n=137) versus insulin aspart 3 times daily in combination with insulin detemir once daily (n=138) versus insulin detemir alone once daily (n=137), aiming at HbA1c ≤7.0% (≤53 mmol/mol). Outcomes: Primary outcome was change in mean carotid IMT (a marker of subclinical cardiovascular disease). HbA1c, insulin dose, weight, and hypoglycaemic and serious adverse events were other prespecified outcomes. Results: Carotid IMT change did not differ between groups (biphasic −0.009 mm (95% CI −0.022 to 0.004), aspart+detemir 0.000 mm (95% CI −0.013 to 0.013), detemir −0.012 mm (95% CI −0.025 to 0.000)). HbA1c was more reduced with biphasic (−1.0% (95% CI −1.2 to −0.8)) compared with the aspart+detemir (−0.4% (95% CI −0.6 to −0.3)) and detemir (−0.3% (95% CI −0.4 to −0.1)) groups (p<0.001). Weight gain was higher in the biphasic (3.3 kg (95% CI 2.7 to 4.0) and aspart+detemir (3.2 kg (95% CI 2.6 to 3.9)) compared with the detemir group (1.9 kg (95% CI 1.3 to 2.6)). Insulin dose was higher with detemir (1.6 IU/kg/day (95% CI 1.4 to 1.8)) compared with biphasic (1.0 IU/kg/day (95% CI 0.9 to 1.1)) and aspart+detemir (1.1 IU/kg/day (95% CI 1.0 to 1.3)) (p<0.001). Number of participants with severe hypoglycaemia and serious adverse events did not differ. Conclusions: Carotid IMT change did not differ between 3 insulin regimens despite differences in HbA1c, weight gain and insulin doses. The trial only reached 46% of planned sample size and lack of power may therefore have affected our results. Trial registration number: NCT00657943.